PENERAPAN MODEL PEMBELAJARAN LANGSUNG UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKASISWA KELAS IV SD NEGERI 001 SAWAH BARU KECAMATAN KAMPAR TIMUR - Suharti, Suharti; Syahrilfuddin, Syahrilfuddin; Marhadi, Hendri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract:The problem this research is the students achievement of mathematics studies still low with an average value of 62,32 and minimum completeness criteria (KKM) mathematics studies is 65. Between students, amounting to 28 people only 12 students whoachieve classical KKM with 42,86%.This research is Classroom Action Research, which aims to improve thestudents achievement of mathematics studies class IVat SDN 001 Sawah Baru Kec. Kampar Timur with implementation of model pembelajaran langsung.Formulation of the problem: Is the implementation of pembelajaran langsung can improve the students achievement ofmathematics studies class IVat SDN001 Sawah Baru Kecamatan Kampar Timur.Subjek were students of SDN 001 Sawah Baru Kec. Kampar Timur, totaling 28 people.The data collection instrumentis ateacher and student activities sheets and students achievement. Results obtained each day before the action an improve in base score cycle with the average being 62,32 and merease in cycle I to 76,07 and in the cycle II increased to 87,86. In cycle I, the first meeting of the theacher activities gained 65%, the second meeting of the percentage increased to 75%. In cycle II, the first meeting of the percentage to 80%, at the second meeting of the percentage increased to 95%. Activities of students in the learning process in cycle I, first meeting gained 70%, the second meeting of the percentage increased to 75%. In cycle II, the first meeting of the percentage to 85%, at the second meeting of the percentage increased to 95%.The result showed that the implementation of model pembelajaran langsung can improve the students achievement of mathematics studies.Key Words: Direct Learning, Achievement of Mathematics Studies